Modification of Starch Talas Beneng (Xanthosoma Undipes K. Koch) with Oktenil Suksinat Anhydrous (Osa) and its application in Mayonaise - Saadah, Fatihatus; Fitrina, Neneng; Rosidah, Yusi; Majda, Laila; Abidin, Zainal (Eximia, 2021)
Taro beneng is one of the plants that has a high starch content. This resulting natural starch has several drawbacks so modification is needed. This study aims to determine the optimum concentration and pH of OSA in taro starch modification so as to produce the best OSA starch, determine the characteristics of the modified starch, and determine the best formula in the process of making mayonnaise products by using OSA starch as an emulsifier that can produce high-quality mayonnaise. The process of modification of starch with OSA is carried out esterification with a concentration of OSA 1%; 3%; 5% and pH 7.5; 8,5; 9.5. The modifications were tested for DS, amylose content, starch digestibility, development power, emulsion capacity, solubility, SEM, XRD, DSC, and RVA. Then OSA starch is best used in the manufacture of mayonnaise by determining the best formula that can produce mayonnaise with the best pH, fat content, emulsion stability, viscosity, color, and organoleptic. The results showed that OSA starch was best obtained by esterification process using OSA 3% and pH 8.5 with characteristic DS value of 0.0270; amylose content of 20.35%; starch digestibility 187.39%; degree of krisatalinitas 41,7%; peak viscosity 4171 cP; development power of 7.2117 at 90_C and solubility of 76.50% at 90_; granule size 2,077 _m - 3,435 _m with porous and rough polygonal shape; has a crystalline structure of pattern A; _H 132 (J/g) at a peak temperature of 96.38_C; and a peak viscosity of 4171 cP at a final temperature of 79.90 _C. Mayonnaise is best obtained at the addition of 1% OSA starch and 4% egg yolk with a pH value of 3.1; fat content of 37.57%; emulsion stability 64.69%; emulsion viscosity 44625 cP; and color brightness of 94,325.